Leadership And Strategic Management At Army Polytechnic - Rachmat Setiawibawa (Pusat Riset dan Inovasi Nasional, 2022)
Leadership is the strength, skill or ability that exists within a person to influence and lead other people, with the aim of achieving predetermined targets (goals). Leadership can also be defined as a management function to influence, motivate, or direct other people to do certain things to achieve certain goals. An Army Polytechnic Leader is someone who is given the status of leading an Army Polytechnic based on selection and assignments given by the Indonesian Ministry of Defense. A person selected to be a leader is an individual who is able to influence, encourage, invite, guide, mobilize and direct individuals in the organization so that they can receive their influence in order to achieve the goals of the Army Polytechnic.